2021
DOI: 10.1155/2021/8893563
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Anti-Inflammatory Activities of Sophocarpine from Sophora viciifolia Hance

Abstract: Sophora viciifolia Hance is an edible plant used in traditional Chinese medicine. Sophocarpine, a tetracyclic quinolizidine alkaloid, is one of the most abundant active ingredients in Sophora viciifolia Hance. Here, we study the analgesic and anti-inflammatory effects, as well as the acute toxicity of sophocarpine from Sophora viciifolia Hance in mice. Sophocarpine (20, 40, and 80 mg/kgbw) significantly prolonged the delay period before a hot plate reaction occurred (all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Due to the fact that few of the permitted kidney-injury-specific therapeutic approaches are available at present, it is urgent for us to identify and develop novel and effective therapeutic approaches for kidney injury. Sophocarpine (SOP) is a tetracyclic quinolizidine alkaloid extracted from Sophora flavescens, and shows a variety of biological characteristics such as anti-inflammatory, anti-tumor, anti-nociceptive, neuroprotective and immune regulatory properties [5][6][7][8][9]. It has been reported that sophocarpine could attenuate liver injury by suppressing oxidative stress, inflammation and apoptosis [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the fact that few of the permitted kidney-injury-specific therapeutic approaches are available at present, it is urgent for us to identify and develop novel and effective therapeutic approaches for kidney injury. Sophocarpine (SOP) is a tetracyclic quinolizidine alkaloid extracted from Sophora flavescens, and shows a variety of biological characteristics such as anti-inflammatory, anti-tumor, anti-nociceptive, neuroprotective and immune regulatory properties [5][6][7][8][9]. It has been reported that sophocarpine could attenuate liver injury by suppressing oxidative stress, inflammation and apoptosis [10].…”
Section: Discussionmentioning
confidence: 99%
“…into the mice belonging to this group once per day over two weeks, followed by intraperitoneal stimulation of ISO (10 mg/kg) for another two weeks. The dosage and procedure of the reagent administration were carried out according to previous research [6,30]. Approval for the treatment protocols was obtained from the Animal Care and Use Committee of the Second Affiliated Hospital of Nanchang University (China).…”
Section: Animal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For 20 mints, acid-induced writhes were counted. For counting purpose, a writhe was described by at least one hind limb stretching or simultaneous stretching of the abdomen (Wang et al, 2021).…”
Section: Writhing Testmentioning
confidence: 99%
“…Pain is usually associated with inflammation. In pain associated with inflammatory conditions (like rheumatoid arthritis, osteoarthritis, and inflammatory bowel disease), various inflammatory mediators like interleukin 6 (IL‐6), nitric oxide (NO), bradykinins, and prostaglandins (PGs) among others are released and stimulate nociceptors leading to hyperalgesia (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%